Unjuk Kerja Mesin Perajang Biomassa Tipe Slicer untuk Perajangan Pelepah Kelapa Sawit - Hafizh, Galang Dzakwan; Asmara, Sandi; Oktafri, Oktafri; Suharyatun, Siti (abe.fp.unila.ac.id, 2026)
This study aimed to evaluate the performance of a slicer-type biomass chopper in processing oil palm fronds at different engine speeds (2000, 2350, and 2700 rpm). The observed parameters included working capacity, fuel consumption, material losses, and ergonomic aspects. The results showed that variations in engine speed significantly affected machine performance. The highest working capacity was achieved at 2700 rpm, reaching 465.96 kg/h, while the lowest was at 2000 rpm with 185.04 kg/h. Fuel consumption ranged from 1.29 to 1.70 L/h, with the lowest value at 2000 rpm and the highest at 2700 rpm. The lowest material loss was recorded at 2000 rpm (0.95%), whereas the highest occurred at 2700 rpm (2.44%). Ergonomic analysis indicated that the Cardiovascular Load (CVL) ranged from 31% to 36%, categorized as moderate workload and still tolerable for operators. Overall, the best performance was obtained at 2700 rpm due to its highest working capacity with relatively acceptable losses.